Utility of immunohistochemical staining for the diagnosis of Extra-adrenal mediastinal paraganglioma - Metelmann, Isabella B. (Respir Med Case Rep, 2020)
Extra-adrenal, mediastinal paraganglioma are rare tumors that origin from sympathetic ganglia. Common diagnostic steps include CT, MRI and PET-Scan. We present a case where immunohistochemical staining was an essential step for final diagnosis in a patient without symptoms of endocrine activity and an uncommon location of this tumor entity. In combination with clinical particularities on the origin of the tumor and characteristic morphology, the immunohistochemical staining of tumor tissue is a necessary diagnostic tool for paraganglioma.